The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.17957/ijab/15.0178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Tillage Practices on Soil Physical Properties and Wheat Performance in Different Wheat-based Cropping Systems

Abstract: Excessive tillage in conventional agriculture systems may cause plough pan, which alters soil physical properties, and thus adversely affects the crop growth and productivity. This study was conducted to monitor the effect of different tillage practices in wheat-based cropping systems on soil physical properties, allometry and grain yield of wheat. Wheat was planted in different cropping systems (viz. fallow-wheat, rice-wheat, cotton-wheat, mungbean-wheat and sorghum-wheat with zero tillage, conventional tilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…During initial stages the growth of main root axis of plant is badly affected in zero tilled plots owing to change in soil physical properties (Lampurlanes et al, 2001) which may limit the nutrient and water uptake by plants (Qin et al, 2006). Therefore, in this study, zero tilled wheat observed decrease in crop allometric traits because of these limitations (Shahzad et al, 2016a). However, improvement in allometric traits from osmoprimed seeds was due the emergence of more healthy and vigorous seedlings.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…During initial stages the growth of main root axis of plant is badly affected in zero tilled plots owing to change in soil physical properties (Lampurlanes et al, 2001) which may limit the nutrient and water uptake by plants (Qin et al, 2006). Therefore, in this study, zero tilled wheat observed decrease in crop allometric traits because of these limitations (Shahzad et al, 2016a). However, improvement in allometric traits from osmoprimed seeds was due the emergence of more healthy and vigorous seedlings.…”
Section: Discussionmentioning
confidence: 63%
“…Regular use of tillage practices to craft fine seedbed for wheat (Triticum aestivum L.) planting leads to the formation of plough pan (Islam et al, 2005;Bertolino et al, 2010) which may affect crop performance due to altered soil physical properties and increasing penetration resistance to developing roots (Shahzad et al, 2016a). Moreover, this plough pan is found to be shallower than usual rooting depth and thus may act as a hurdle for roots either due to lesser porosity or higher root penetration resistance (Bruand et al, 2004;Shahzad et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Küstermann et al (2013) examined the effects of a conventional and reduced treatment with different N rates on wheat (Triticum aestivum L.) yield in a crop rotation with potatoes; they collected data that indicated that conventional tillage (CT) at low and medium N rates produced higher wheat yields than (RT). These significantly higher wheat yields achieved in the CT system compared with RT are reported by Shahzad et al (2016). Moraru and Rusu (2012) examined the influence of CT, RT, and sowing with no-tillage (NT) and suggest that differences in wheat yield with these systems are nonsignificant.…”
Section: Introductionmentioning
confidence: 90%